Tinjauan Yuridis Terhadap Proses Penerbitan Akta Kelahiran Anak Luar Kawin (Studi Dinas Kependudukan dan Catatan Sipil Kabupaten Batu Bara) - Banun, Sri; Azmi, Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Children who are state assets who will continue the nation's ideals, it is only right that we as adults and have a healthy mind fight for their rights so that they can grow and develop properly so that there is no more discrimination against the position of illegitimate children who are human beings with inherent dignity and dignity from the womb to death as stated in Law No. 39 of 1999 concerning Human Rights, with a study entitled